Perencanaan Strategi Untuk Mengurangi Produk Reject Dengan Pendekatan Lean Manufacturing - Suguanto, Suguanto; Natigor Nasution, Fahmi; Muluk, Chairul (Value : Jurnal Manajemen dan Akuntansi, 2024)
Company X, a feed manufacturer, faced a significant challenge related to a high product rejection rate of 10%. This study aimed to identify the root causes of the problem and implement lean manufacturing-based solutions to reduce waste. Through fishbone and Pareto analysis, the study revealed that human errors and non-standard measuring instruments were the primary contributors to the issue. The PDCA cycle was utilized as a framework for implementing solutions. The results demonstrated that the company reduced the product rejection rate by improving employee adherence to production procedures and conducting regular calibrations of measuring instruments. This research highlights the importance of lean manufacturing approaches in optimizing production processes and enhancing product quality in the feed industry.